Symposium 9: Researching networked learning generatively - Schaverien, Lynette; Alexander, Shirley (Proceedings of the International Conference on Networked Learning, 2008)
The late C20th and C21st brought advances in the natural sciences and in ways of thinking about complex dynamic self-organising systems, yielding a powerful, state-of-the-art learning theory. According to this biologically based generative theory, learning (or knowledge-gaining) can be viewed as an adaptation, hedging our species’ chances of survival. Hence, we can recognise learning (as it is conventionally understood, for individuals and cultures) as being at one with what we might call the “genetic knowledge” passed on by way of our genes in natural selection. This selectionist view of learning leads us to think about learning as generating ideas, testing them on their value and keeping those that survive these tests. The emergent field of networked learning depends for its survival, at least at two levels, on the development of robust learning theory. First, if networked environments are to succeed in supporting learning, there is a need for principled learning design. Second and much less widely recognised, research itself is a paradigm case of learning. So, it stands to reason that approaches to researching networked learning must also be theoretically defensible. We begin this paper by describing this biologically-based generative theory of learning, identifying its three central characteristics and showing how these are aligned with six acts of learning: exploring, designing, making, operating, explaining and understanding. We justify the worth of this theory, first by brief reference to key educational thinkers whose work might now be considered presciently generative, and then by illustrating the power of this theory in explaining learning, from our research group’s sustained empirical testing of this theory in a variety of face to face and networked learning contexts. We also note the success of this theory in distilling design parameters for learning opportunities, including in networked learning. Our principal focus in this paper is on how a research methodology for investigating learning (including networked learning) emerges from this generative learning theory. We illustrate this methodology by way of a recent Australian Research Council supported, industry-linked project in which both authors were Chief Investigators: the GENESIS project (Generating e-Learning Systems in Schools). That project explored the worth of casting young learners as designers of a networked learning environment, as a novel way of helping their schools to understand and embed some educationally fruitful networked learning approaches. Not only did these young students assume control over generating the curriculum content, but also the conception and, as far as possible, the testing of their ideas through prototyping and evaluation of the resulting networked learning environment. We describe the GENESIS project and locate it as a particular kind of design-based research, in which an integrated theory-practice cycle allows enhancement of the networked learning environment and the generative theory on which it was based. We examine the project’s research design for evidence of the three central features that would allow us to conclude that it is generative in nature. Such scrutiny affirms that the GENESIS project employed an inherently generative research methodology. In conclusion, we assert that generative learning theory is still controversial in Education. However, it enables a focus on what learners (rather than teachers) do and it can account for creativity. In a political climate that increasingly values innovation, we speculate that generative methodologies may well constitute a crucial step towards principled research into networked learning.